Marine propellers and propulsion - Eckstein, Alfred (Scitus Academics, 2017)
Marine propellers and propulsion provides comprehensive and progressive coverage to furnish marine engineers, naval architects and anyone involved in propulsion and hydrodynamics with knowledge needed to do the job.